The impact of occupational health service network and reporting system in Taiwan. (1st October 2013) - Chu, Po-Ching; Fuh, Hwan-Ran; Luo, Jiin-Chyuan; Du, Chung-Li; Chuang, Hung-Yi; Guo, How-Ran; Liu, Chiu-Shong; Su, Chien-Tien; Tang, Feng-Cheng; Chen, Chun-Chieh; Yang, Hsiao-Yu; Guo, Yue Leon
<x xml:space="preserve">Abstract</x> Background: Underreporting occupational disease cases has been a long-standing problem in Taiwan, which hinders the progress in occupational health and safety. To address this problem, the government has founded the Network of Occupational Diseases and Injuries Service (NODIS) for occupational disease and injury services and established a new Internet-based reporting system. Objectives: The aims of this study are to analyze the possible influence of the NODIS, comprised of Center for Occupational Disease and Injury Services and their local network hospitals, on compensable occupational diseases and describe the distribution of occupational diseases across occupations and industries from 2005 to 2010 in Taiwan. Methods: We conducted a secondary analysis of two datasets, including the NODIS reporting dataset and the National Labor Insurance scheme's dataset of compensated cases. For the NODIS dataset, demographics, disease distribution, and the time trends of occupational diseases were analyzed. The data of the Labor Insurance dataset was used to calculate the annual incidence of compensated cases. Furthermore, the annual incidence of reported occupational diseases from the NODIS was further compared with the annual incidence of compensable occupational diseases from the compensated dataset during the same period. Results: After the establishment of the NODIS, the two annual incidence rates of reported and compensable occupational disease cases have increased by 1·2 and 2·0 folds from 2007 to 2010, respectively. The reason for this increased reporting may be the implementation of the new government-funded Internet-based system. The reason for the increased compensable cases may be the increasing availability of hospitals and clinics to provide occupational health services. During the 2008-2010 period, the most frequently reported occupational diseases were carpal tunnel syndrome, lumbar disc disorder, upper limb musculoskeletal disorders, and contact dermatitis. Conclusions: The new network and reporting system was successful in providing more occupational health services, providing more workers with compensation for occupational diseases, and reducing underreporting of occupational diseases. Therefore, the experience in Taiwan could serve as an example for other newly developed countries in a similar situation.